Embodied leadership: The aesthetics of gesture. (August 2013) - Bathurst, Ralph; Cain, Trudie
This paper proposes that leadership is an embodied process which occurs among those who are in community together. This implies that the dualities between the leader and the follower morph into a set of relationships where bodies move and gesture to one another by inviting and responding to each other in open co-creative spaces. To work through our ideas, we offer an exemplar of Richard Strauss's song Morgen! as it is rendered in performance. We locate our study within the theory of relational leadership and suggest that effective leadership draws on the abilities of organisational members to offer and respond to gestures as they occur moment-by-moment.